Prevalence and clinical characteristics of human CoV-HKU1 in children with acute respiratory tract infections in China - Jin, Yu (J Clin Virol, 2010)
BACKGROUND: Human CoV-HKU1 (HCoV-HKU1) has been isolated from a 71-year-old man with pneumonia; however, the impact and role of emerging HCoV-HKU1 have not been defined in children with acute respiratory tract infection (ARTI). OBJECTIVE: To investigate the Prevalence and clinical characteristics of HCoV-HKU1 in children with ARTI in Lanzhou, China. STUDY DESIGN: The reverse transcription polymerase chain reaction (RT-PCR) or PCR was employed to screen HCoV-HKU1 and other common respiratory viruses in 645 nasopharyngeal aspirate (NPA) specimens collected from children with ARTI from November 2006 to October 2008. All PCR positive products were sequenced. And the demographic and clinical data were collected for all patients. RESULTS: Nineteen of 645 (2.95%) specimens tested positive for HCoV-HKU1, and all HCoV-HKU1 positive specimens were distributed in the winter and spring season. The HCoV-HKU1 co-infection rate with other respiratory viruses was 47.37% (9/19). There was no statistically significant difference in the detection rate between groups by age or gender, except between patients with and without underlying diseases. The phylogenetic analysis indicated that HCoV-HKU1 genotype B was circulating in the years 2007 and 2008 in children with ARTI in Lanzhou, China. CONCLUSIONS: HCoV-HKU1 is an uncommon virus existing among Chinese children with ARTI. Children with underlying diseases are more vulnerable to viral infection. Only HCoV-HKU1 genotype B circulated locally.